2010
DOI: 10.1017/s0144686x1000019x
|View full text |Cite
|
Sign up to set email alerts
|

New networked technologies and carers of people with dementia: an interview study

Abstract: Dementia is one of the greatest contemporary health and social care challenges, and novel approaches to the care of its sufferers are needed. New information and communication technologies (ICT) have the potential to assist those caring for people with dementia, through access to networked information and support, tracking and surveillance. This article reports the views about such new technologies of 34 carers of people with dementia. We also held a group discussion with nine carers for respondent validation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 17 publications
4
48
0
2
Order By: Relevance
“…Similar views were expressed by informal carers in another investigation, where network technology was considered to be something that would be more useful for the next generation [11]. In the same study, the necessity of having more information was also pointed out, as was a need for training and for ongoing support to enable those for whom the technology was intended to use it; again, this agrees with the statements made by the participants in the current research.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar views were expressed by informal carers in another investigation, where network technology was considered to be something that would be more useful for the next generation [11]. In the same study, the necessity of having more information was also pointed out, as was a need for training and for ongoing support to enable those for whom the technology was intended to use it; again, this agrees with the statements made by the participants in the current research.…”
Section: Discussionsupporting
confidence: 85%
“…Different "digital solutions" have the potential to meet some of the needs of people with cognitive impairments and can be used to improve the quality of life of the ageing person with mild dementia [10][11][12]. Benefits like increased independence and a greater feeling of wellbeing are described leading to an improved quality of life brought about by the use of assistive digital devices [2,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The right technologies used at the right times can be useful, but providing early information about these technologies to people with dementia and their relatives can facilitate joint decision--making about their use. And Powell et al [2010] reported the challenges perceived by caregivers about the introduction of computing technologies into dementia care -challenges that included the need to balance power and autonomy whilst maximising safety, reduce personal contact and complement rather than replace care activities.…”
Section: Related Workmentioning
confidence: 99%
“…Interactive e-Health support services for caregivers have yet to become widely used in real-life healthcare situations in the dementia care setting. Based on the identified user needs, a result of a carefully and comprehensively determining the necessary requirements capture (which has been emphasized in previous studies [10, 12, 1821]), the eHM Dementia Portal (eHM-DP) was developed for the home-based dementia care setting [22]. To our knowledge, our study is the first of a personalized and interactive web portal, aiming at empowerment and decision aid while considering the perspectives of caregivers and MPs.…”
Section: Introductionmentioning
confidence: 99%